Feeding of baikal seal Pusa sibirica Gm. on pelagic crustacean Macrohectopus branickii Dyb. in conditions of artificial lighting - E. A. Petrov; A. B. Kupchinsky (Известия ТИНРО, 2024)
Behavior of baikal seal Pusa sibirica Gm. at the depth of 200 m under permanent artificial illumination was filmed for the first time using stationary videocameras. Several seals found dense aggregations of prey concentrated in the illuminated sector presented mainly by adult females of pelagic crustacean Macrohectopus branickii Dyb. For many days, the seals actively hunted on M. branickii, rarely on fish, as juvenile pelagic golomyanka Comephorus sp. and coastal-pelagic Cottoidei. Their feeding behavior is described, as hunting techniques, methods of prey capturing, feeding activity of seals and behavior of the prey. The constant illumination disrupted natural vertical daily migrations of the crustacean and so changed the strategy of food diving for baikal seal. Based on the new obtained data, the hypothesis of Japanese scientists on decisive role of M. branickii in diet of baikal seal and high importance of this food resource for prosperity of the population is criticized. Such hypothesis supposes stable dense aggregations of the crustacean with abundant adult females of late generation (comparable with those under artificial light) in the pelagic layer of Lake Baikal at the depths accessible to seals, easy found by seals, but these conditions are never observed in nature.